Manipulation of microparticles in microfluidic channel by surface acoustic wave - An, Minglei (2019)
Microfluidic manipulation technology refers to precise control of the motion state of microparticles, such as capturing, screening, moving, and classifying cells, biomacromolecules, and nanomedicines. It has important applications in biomedical, chemical analysis, and materials science. It has aroused great concern from scholars all over the world. Acoustic manipulation uses sound waves to manipulate particles, which has advantages of non-contact, good penetrability, and no chemical modification to the particles. In recent years, with the rapid development of micro-electromechanical systems (MEMS) and microfluidic chips, surface acoustic wave (SAW)-based micro-manipulation technology has received extensive attention and research.